Technology deployment in physics lessons: Understanding optics better with Augmented Reality. Issue 1 (May 2021) - Stolzenberger, Ch; Wolf, N; Trefzger, T
Abstract: The following article presents the results of a seminar on "Augmented Reality in Institutional Education". There, together with STEM trainee teachers, an optics experimentation circle was developed for pupils in the 7th and 8th grade at the Gymnasium for the subject of "Nature & Technology" or "Physics". This includes (real) experiments (lunar phases / eclipses, refraction, refractive error, color mixing), which were enriched with Augmented Reality technology created by the students. By creating a learning scenario with the help of Augmented Reality at school, the real environment continues to be perceived by the students but is supplemented with visualizations of physical model concepts. For example, the refraction of laser light on a water surface in the real experiment was overlaid with a visualization of the physical ray model of light, so that both information can be perceived simultaneously. This offers the students the opportunity to link physical model concepts statically but also in their spatial or temporal change in conjunction with the real experiment and to actively interact with it at the same time. Even without linking to a real object, augmented reality makes it possible to visualize changing processes or three-dimensional movements of virtual objects and to integrate holograms into the real world. We hope that the experiments presented here can demonstrate the benefits of AR extensions to real experiments, so that more applications will find their way into STEM lessons in the future.